Strengthening Links between Social Protection and Disaster Risk Management for Adaptive Social Protection in Nepal - World Bank (World Bank, Washington, DC, 2019)
A key challenge in Nepal is the intersection of predictable chronic or seasonal poverty andvulnerability, with rapid-onset and acute shocks. Nepal in the last few decades has epitomized the'perfect storm' in which a number of different factors—disasters, conflict, political uncertainty, and challenges to economic growth—coincide with deleterious effects on people's well-being anddevelopment progress. While social protection (SP) is playing an increasing role in tackling chronic and seasonal poverty and wider vulnerability and exclusion, recent disasters in Nepal, particularly in 2015, highlight how making SP more flexible and adaptive could allow a more effective and efficient development and humanitarian response. The World Bank in Nepal contracted the Centre for International Development and Training at the University of Wolverhampton, United Kingdom, and the Nepal Institute for Social and Environmental Research, to carry out the technical assistance (TA) project 'Review of policies, systems and programs in social protection and shock response for adaptive social protection in Nepal'. The overall objective of the work is to make recommendations on possible policy, programmatic, and institutional measures for more adaptive social protection (ASP). The analysis was delivered using a mixed-methods approach. An analysis of existing data (including the Household Risk and Vulnerability Survey [HRVS] data) was used to understand the scope and coverage of existing programs and their links to disasters and shocks. A desk review of literature explored legislation and policies, program documentation and official implementation guidelines, and evaluations and research. Interviews took place with key informants at the national, district, and local government levels as did focus group discussions (FGDs) and individual interviews, especially with recipients of SP programs, at the ward or village level in the districts of Bardiya, Humla, Saptari, and Sindhupalchok.